Методи насіннєвого та клонального мікророзмноження ендема о. Мадагаскар – Angraecum eburneum Bory (Orchidaceae Juss.) - Cherevchenko, T.M.; Buyun, L.I.; Lavrentyeva, A.M.; Ivannikov, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Results of researches on working out of methods seed and clonal reproduction of Angraecum eburneum Bory are given. Nutrient mediums for all stages of microreproduction are picked up. Optimum explants and them morphogenic potential are defined.